Brain natriuretic peptide in decompensation of liver cirrhosis in non-cardiac patients - Radvan, Martin; Svoboda, Petr; Radvanová, Jana; Štumar, Josef; Scheer, Peter (Hepato-gastroenterology, 2009)
BACKGROUND/AIMS: Brain natriuretic peptide is recently widely used as a diagnostic and prognostic marker of heart failure. Plasma levels of this peptide are elevated in other, non-cardiac conditions as well, among others in liver cirrhosis, especially presenting with fluid retention and,--ascites. METHODS: Circulating levels of BNP was determined in 25 non-cardiac patients, 20 men, 5 women admitted at our medicine department from March 2006 to September 2007 with decompensate ascitic liver cirrhosis. Severity of disease was measured by Child and MELD (Model of End Stage of Liver Disease) score. RESULTS: Plasma BNP was increased in our patients (range 21-1078 pg/ml) and significantly correlated with the severity of liver failure assigned as Child's classification (r = 0.51; p = 0.009) and MELD score (r = 0.56; p = 0.003) as well as with the glomerular filtration rate (r = -0.62; p = 0.0009). Four patients with initial BNP > 600 ng/L died, while all 21 patients with BNP < 600 ng/L survived (p = 0.0019). CONCLUSION: B-type natriuretic peptide in plasma correlated significantly with the severity of liver disease in cirrhotic patients. High plasma BNP seems to be a good negative prognostic factor of the death in cirrhosis.
Keywords: Regression Analysis; dospělí; Female; biologické markery; Liver Cirrhosis; Biomarkers; Adult; ženské pohlaví; jaterní cirhóza; lidé; Natriuretic Peptide, Brain; regresní analýza; míra přežití; stupeň závažnosti nemoci; neparametrická statistika; natriuretický peptid typu B; Male; Aged; Survival Rate; lidé středního věku; Statistics, Nonparametric; senioři; mužské pohlaví; Severity of Illness Index; Middle Aged; Humans